Transformation of Women's Leadership in Pesantren from Fiqh Siyāsah Perspective: Social Dynamics in the Patriarchal Culture of South Sulawesi - Fatmawati, Fatmawati; Amir, Rahma; Alamsyah, Anggriani; Ilham, M. (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This research aims to explore the assessment of fiqh siyāsah regarding the role of women’s leadership in Islamic boarding schools (pesantren) in South Sulawesi and how the patriarchal cultural structure and the existence of bissu influence this dynamic. The study is empirical, employing the approach and theory of fiqh siyāsah. Primary data were collected through interviews with several prominent figures, while secondary data were obtained from literature studies. Data collection involved techniques such as interviews, participatory observation, and documentation within the pesantren. The findings indicate that although women are beginning to play leadership roles within a limited context, the influence of patriarchal culture still dominates the highest policy-making processes in the pesantren. Conversely, the presence of bissu as a ceremonial figure recognized by the community significantly contributes to the acceptance of women in the realm of religious education. The originality of this research lies in its comprehensive analysis of the interaction between local culture and women’s leadership, as well as the role of bissu in opening opportunities for women. The implications of these findings underscore the importance of applying the principles of fiqh siyāsah that emphasize justice and equality, and how this can support women's roles in creating a more just and inclusive society. This study provides a new perspective that enriches the discussion surrounding women's leadership amidst the patriarchal culture of South Sulawesi.